Formulation of Facial Wash Gel from Kalamansi Orange (Citrusn microcarpa) Peel Extract as an Antioxidant for Facial Skin Care - liany carolina rambu lika; Liandhajani (Jurnal FARMASIMED (JFM), 2025)
Cosmetics are preparations used on the outer layer of the human body to cleanse, perfume, beautify, and maintain the body in good condition. Free radicals are reactive oxygen species with unpaired electrons that are unstable and can cause cellular damage, leading to degenerative diseases. Antioxidants play an important role in preventing this damage by inhibiting oxidation processes and scavenging free radicals. This study aimed to develop a facial soap gel formulation using calamansi orange peel extract (Citrus microcarpa) as the active ingredient. The extract was obtained through maceration using 96% ethanol and concentrated with a rotary evaporator. The facial soap gel was formulated in three concentrations, namely 1%, 1.5%, and 2%, and its physical properties were evaluated through organoleptic, pH, homogeneity, foaming power, viscosity, spreadability, and hedonic tests. The findings indicate that the calamansi orange peel extract was successfully formulated into a facial soap gel that meets the physical evaluation requirements. Antioxidant activity testing using the DPPH method shows that Formula III exhibits the highest antioxidant activity with an inhibition percentage of 73.75% and an IC₅₀ value of 29.45 µg/mL. Formula III has the potential to be developed as a functional facial soap that not only cleanses but also provides protection against skin damage caused by free radicals.